Survival analysis of a cohort of extremely preterm infants born in Finland during 2005–2013. (3rd August 2021) - Härkin, Pia; Marttila, Riitta; Pokka, Tytti; Saarela, Timo; Hallman, Mikko
Abstract: Objective: This study aimed to analyze the mortality of extremely preterm infants (ELGA born alive before 28 weeks) until the postconceptional age of 42 weeks, death, or home discharge, whichever came first. It was focused especially on studying the relationship between antenatal risk factors, the time of death, and the postnatal morbidities associated with mortality. Study design: The original data obtained from the nationwide Finnish medical birth register of extremely preterm and low birthweight infants born during 2005–2013 were analyzed. The total population consisted of 1353 ELGA infants after the exclusion of 18 infants born with lethal congenital anomalies or genetic defects. Mortality risks were adjusted according to the length of gestation, the administration of antenatal steroids, and the delivery hospital. Results: During the first 48 hours, extreme immaturity was seen to be the prominent cause of death, and intrauterine growth did not influence mortality. The ELGA population surviving for at least 48 hours ( N  = 1135) was submitted for mortality risk analysis. After the adjustments, small-for-gestational-age (SGA) (birth weight below −2 SD) was found to be the factor with the highest risk for demise [OR 6.2; 95% CI (3.9–10.0) p  < .001]. Multiple deliveries were associated with increased risk for death [OR 1.5; 95% CI (1.0–2.1), p  = .048] to a lesser extent. The main neonatal morbidities associated with the risk of mortality after 48 postnatal hours of life were severe intraventricular hemorrhage (IVH) [OR 4.4; 95% CI (3.0–6.7), p  < .001], respiratory distress syndrome (RDS) [OR 2.6; 95% CI (1.3–5.0), p  = .006], and necrotizing enterocolitis (NEC) [OR 2.3; 95% CI (1.5–3.4), p  < .001]. The major morbidities associated with deaths among non-SGA infants were severe IVH (32.1% of all deaths), NEC (19.1%), and sepsis (8.4%). In SGA infants, severe respiratory disease (RDS, severe bronchopulmonary dysplasia, pulmonary hemorrhage, or pulmonary hypertension) was the main cause of death (60.9% of all deaths). Medical or surgical PDA treatment was not found to be associated with increased risk of death [OR 0.4; 95% CI (0.2–0.5), p  < .001] compared to infants who had survived for more than 2 days. Severe preeclampsia was found to be associated with 42% of all ELGA-SGA births. After the adjustments, ELGA infants from pregnancies complicated by preeclampsia of the mother exhibited a significantly lower risk of severe IVH [OR 0.3; 95% CI (0.2–0.5), p  < .001] compared to the non-preeclamptic mothers' infants. The low incidence of severe IVH was evident regardless of fetal growth in this patient group. Conclusions: SGA infants with less than 28 gestational weeks, who had survived for at least 2 days, had excessively high mortality due to severe pulmonary disease. Intrauterine growth had no influence on the risk of death, other than pulmonary causes. The infants of preeclamptic mothers exhibited an increased risk of intrauterine growth retardation; however, despite this serious complication, these infants exhibited a significant decrease in the risk for severe IVH.